EDPEPPS: an integrated environment for the parallel development life-cycle - Delaitre, T.; Zemerly, M.J.; Justo, G.R.; Audo, O.; Winter, S.C. (Future generation computer systems, 2000)
This paper describes an environment for performance-oriented design of portable parallel software. The environment consists of a graphical design tool for building parallel algorithms, a state-of-the-art simulation engine, a CPU characterisation tool, a distributed debugging tool and a visualisation/replay tool. The environment is used to model a virtual machine composed of a cluster of heterogeneous workstations interconnected by a local area network. The simulation model used is modular and its components are interchangeable which allows easy re-configuration of the platform. The model is validated using experiments on two parallel Givens linear solver algorithms with average errors of about 8%.